2022
DOI: 10.1186/s12913-022-07985-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings of a primary care program for individuals recently released from prison: a propensity-matched study

Abstract: Background Criminal justice system costs in the United States have exponentially increased over the last decades, and providing health care to individuals released from incarceration is costly. To better understand how to manage costs to state budgets for those who have been incarcerated, we aimed to assess state-level costs of an enhanced primary care program, Transitions Clinic Network (TCN), for chronically-ill and older individuals recently released from prison. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Numerous chronic non-communicable conditions are represented in the included literature, encompassing diabetes ( n = 11) [ 45 , 49 – 51 , 53 , 55 , 56 , 59 , 60 , 63 , 67 ], gynaecological diseases ( n = 10) [ 26 , 27 , 29 33 , 38 , 43 , 70 ], cardiovascular disease (CVD) ( n = 6) [ 34 , 37 , 42 , 61 , 62 , 83 ], chronic kidney disease (CKD) ( n = 5) [ 35 , 52 , 66 , 72 , 73 ], dermatological conditions ( n = 4) [ 64 , 74 , 78 , 75 ], ophthalmological conditions ( n = 3) [ 57 , 58 , 77 ], respiratory illnesses ( n = 3) [ 48 , 54 , 68 ], oral cancer ( n = 1) [ 25 ], and colorectal cancer ( n = 1) [ 28 ]. Approximately one third of studies ( n = 22) covered several diseases and/or general long-term prisoner health [ 36 , 39 – 41 , 44 , 46 , 47 , 65 , 69 , 71 , 76 , 79 – 82 , 84 89 ]. A minority of research focused on specific populations with prison, including women ( n = 12) [ 26 , 27 , 29 33 , 38 , 42 , 43 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous chronic non-communicable conditions are represented in the included literature, encompassing diabetes ( n = 11) [ 45 , 49 – 51 , 53 , 55 , 56 , 59 , 60 , 63 , 67 ], gynaecological diseases ( n = 10) [ 26 , 27 , 29 33 , 38 , 43 , 70 ], cardiovascular disease (CVD) ( n = 6) [ 34 , 37 , 42 , 61 , 62 , 83 ], chronic kidney disease (CKD) ( n = 5) [ 35 , 52 , 66 , 72 , 73 ], dermatological conditions ( n = 4) [ 64 , 74 , 78 , 75 ], ophthalmological conditions ( n = 3) [ 57 , 58 , 77 ], respiratory illnesses ( n = 3) [ 48 , 54 , 68 ], oral cancer ( n = 1) [ 25 ], and colorectal cancer ( n = 1) [ 28 ]. Approximately one third of studies ( n = 22) covered several diseases and/or general long-term prisoner health [ 36 , 39 – 41 , 44 , 46 , 47 , 65 , 69 , 71 , 76 , 79 – 82 , 84 89 ]. A minority of research focused on specific populations with prison, including women ( n = 12) [ 26 , 27 , 29 33 , 38 , 42 , 43 ,…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies investigated community-based healthcare programmes for people leaving prison, often termed ‘transitions clinics’ [ 81 , 82 , 84 89 ]. These programmes typically involve primary care by physicians in the first two weeks of release, referrals to community organisations, and case management from community health workers (CHW) with histories of incarceration.…”
Section: Resultsmentioning
confidence: 99%
“…The process of such handoffs is intended to reduce apprehension about stigmatizing experiences in the community and to improve engagement in postrelease care. The approach used by the Transitions Clinic Network, with 48 clinics across the country, serves as a model for hiring, training, and supporting a workforce dedicated to health at the time of re-entry ( 48 , 49 ).…”
Section: Operationalization Of An 1115 Miep Waiver To Improve Infecti...mentioning
confidence: 99%
“…Yet, many people return to society without health insurance, doctor’s appointments, medical records, or a continuity of care plan. The Transitions Clinic Network (TCN), a coordinated care model between correctional and community health care systems, has demonstrated that proactive linkages to primary care upon release leads to lower acute care utilization and decreased costs ( 71 , 128 ). Wraparound programs that provide health care and assist with housing, education, and employment are promising interventions for people released from prison ( 35 ).…”
Section: Important Areas Of Focus For Public Health Research and Inte...mentioning
confidence: 99%
“…Wraparound programs that provide health care and assist with housing, education, and employment are promising interventions for people released from prison ( 35 ). Hiring formerly incarcerated community health workers to help people navigate health care and social services during reentry is an essential component of TCN that state public health systems can expand to reduce health inequalities and build bridges between community and correctional health providers ( 71 , 128 ). State officials should revitalize or expand initiatives for ensuring that people are enrolled into insurance programs before release from prison and create capacity in state and local health systems that is tailored to the needs of currently and formerly incarcerated people and their community contexts.…”
Section: Important Areas Of Focus For Public Health Research and Inte...mentioning
confidence: 99%